Incestuous Relations in Bessie Head and Sindiwe Magona: The Perversion of Apartheid and the Migrant Labour System - Gil-Naveira, Isabel (International Journal of English Studies, 2024)
Apartheid and the migrant labour system affected the residential stability of black South African families in terms of wife-husband and father-child relations. The control exerted by apartheid laws made it impossible for generations of fathers for over one and a half centuries to raise their children (Wilson, 2006), affecting their personal and social behaviour. This article contends that in their use of literature as a political tool, writers Sindiwe Magona and Bessie Head offered a similar vision about the father-daughter relationship. Magona’s short story “It was Easter Sunday the day I went to Netreg” (1991) and Head’s short story “The Cardinals” (1995) portray a daughter and a father who do not know each other and who, years later and unknowingly, establish a sexual relation. This article will claim these incestuous relationships can be interpreted as the writers’ representation of the use and abuse the state exerted on its black citizens.